2009
DOI: 10.3171/2009.1.jns0821
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lamina terminalis fenestration in reducing shunt-dependent hydrocephalus following aneurysmal subarachnoid hemorrhage: a systematic review

Abstract: This systematic review revealed no significant association between lamina terminalis fenestration and a reduced incidence of shunt-dependent hydrocephalus. The interpretation of these results, however, is restricted by unmatched cohort differences as well as other inherent study limitations. Although the overall literature supports lamina terminalis fenestration, a number of authors have questioned the technique's benefits, thus rendering its efficacy in reducing shunt-dependent hydrocephalus unclear. A well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 22 publications
0
47
0
3
Order By: Relevance
“…[3][4][5][6][7]11,12,16,18,23 On the basis of the evidence of an association between the severity of SAH and the prevalence of subsequent sNPH, many neurosurgeons have believed that several surgical manipulations for facilitating CSF dynamics, such as hematoma evacuation, widening the opening of the cisterns, and fenestration of the lamina terminalis, might help to reduce the subsequent occurrence of sNPH after the surgical treatment of SAH. However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09).…”
Section: 24mentioning
confidence: 99%
See 4 more Smart Citations
“…[3][4][5][6][7]11,12,16,18,23 On the basis of the evidence of an association between the severity of SAH and the prevalence of subsequent sNPH, many neurosurgeons have believed that several surgical manipulations for facilitating CSF dynamics, such as hematoma evacuation, widening the opening of the cisterns, and fenestration of the lamina terminalis, might help to reduce the subsequent occurrence of sNPH after the surgical treatment of SAH. However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09).…”
Section: 24mentioning
confidence: 99%
“…However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09). 11 On the basis of this evidence, guidelines for the management of chronic hydrocephalus after aneurysmal SAH from the American Heart Association recommend that fenestration of the lamina terminalis not be routinely performed. 2 Another meta-analysis of 5 nonrandomized studies with data from 1718 patients pooled 3 reported that 1336 patients treated with microsurgical clipping had a significantly lower risk of sNPH than 382 patients treated with endovascular coiling (relative risk 0.74; 95% CI 0.58-0.94; p = 0.01); however, 3 of the 5 studies found no significant difference between clipping and coiling for the predictive risk of sNPH.…”
Section: 24mentioning
confidence: 99%
See 3 more Smart Citations